Analysis of Theil Comparative Decomposition Index to Measure Regional Inequality Due to Industrialization Residues - Susanto, Deni Aditya; Wijaya, Oki; Ardiana, Wiwik; Tantiana, Tantiana (Gorontalo State University, 2024)
The Industrial sector in Kendal County, Indonesia, is one of the national strategic projects aimed at promoting investment accumulation and job creation. Unfortunately, the rapid development of this Industrial sector has resulted in income inequality compared to other sectors. This research aims to examine and measure the contribution of the Industrial sector in Kendal County to aggregate inequality. Methodologically, this research uses a quantitative descriptive approach, which involves indexing inequality to reveal economic phenomena. The inequality indices include the Gini ratio index, the Williamson index, and the Theil index. In Kendal County, inequality is at a moderate to high level, as evidenced by a Gini ratio index of 0.411 and a Williamson index of 0.775. On the other hand, the Theil index reaches 0.519, placing it in between the Gini ratio and the Williamson index. The high inequality in Kendal County is attributed to the Industrial sector, accounting for 41.19%. The Industrial sector significantly contributes to the widening of inequality in Kendal County. This is due to the Industrial sector attracting production input factors such as investments, resources, human capital, monetary conditions, and technological innovation. However, the trickle-down effect does not occur between the Industrial sector and other economic sectors such as agriculture, food and beverages, trade, services, and accommodation.